Perancangan Alat Pengepresan Jenang Dengan Metode Anthropometri Dan Ergonomi (Studi Kasus di UKM Agape Pemalang) - Yohanes Antoni (Jurnal Ilmiah Dinamika Teknik, 2015)
Good product design is by paying attention kenyamann side with reference to the approach anthtropometri and ergonomics. Pressing tool porridge in UKM AGAPE Pemalang still use simple tools require workers to manually by tapping molten metal that has been cooked with wood Entong aid as a tool to smooth porridge. Many weaknesses by using the tool before pressing molten metal which causes rapid fatigue menjdi workers. In this scheme using anthropometric and ergonomic approach in determining the level of worker comfort. Samples used from 31 employee. From this study it can be concluded that the presence of molten metal stamping tool worker more comfortable in using the tool, but it is more effective than the previous tool. The advice that can be given is to pay more attention creations, creativity, innovation, and comfort level working with the concept in order to generate results ergonomic design a good product. In the design of the product in addition to the ergonomic size also must pay attention to in terms of strength and safety during use. Keywords: Pressing Tool porridge, Product Design, Anthropometri